PENINGKATAN PEMAHAMAN PENELITI MENGENAI ASUMSI FILOSOFIS “POSITIVIST SOCIAL SCIENCE” DALAM PEMILIHAN DESAIN PENELITIAN KUANTITATIF - Abdillah, Muhammad Rasyid; Anita, Rizqa; Fadhilla, Mutia (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
Understanding the philosophical assumptions in social research, whether “positivist” or “interpretive,” is crucial as these foundations shape the way researchers approach, design, and conduct their studies, impacting every aspect from the selection of research design to the interpretation of findings. This community service activity (PKM) focused on enhancing young researchers' understanding of “positivist social science” (PSS) assumptions in selecting quantitative research designs at PTN XYZ, a public university in Riau Province. Discussions with a faculty leader revealed difficulties in publishing quantitative research in reputable international journals, primarily due to a lack of understanding of these philosophical assumptions. To address this, the PKM team organized online training for 18 researchers, covering key topics such as the philosophical foundations of science, PSS approaches in social science, reasons for the acceptance or rejection of research reports by the scientific community, and the research process in quantitative design. The effectiveness of the training was evaluated using a pretest-posttest approach, with initial findings showing only 5% of participants correctly understood the reasons for using a quantitative design. However, post-training results indicated a significant improvement in participants’ knowledge, ensuring the research contributes meaningfully and relevantly to the field. Keywords: Philosophical assumptions, positivist social science approach, quantitative